2017
DOI: 10.3928/01477447-20170223-02
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Total Knee Arthroplasty After Prior Microfracture: A Matched Cohort Study

Abstract: Microfracture (MFX) is a common operation for articular cartilage lesions. Data for patients who underwent total knee arthroplasty (TKA) after previous MFX are limited. The purpose of this study was to determine the outcomes, complications, and factors that influence outcomes in patients with previous MFX compared with those without previous MFX. Between 2005 and 2014, twenty-one TKAs were performed at a single tertiary care academic institution in patients with prior history of MFX surgery. These patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…Significantly lower KOOS Symptoms, Pain, and QoL subscores after knee arthroplasty were demonstrated in the previous cartilage cohort. This concurs with the findings of Ansari et al [11] in a cohort of 21 previous microfracture patients with a mean 7.8 points lower improvement in the Knee Society Score (KSS) in the cartilage cohort than in a matched group of knee arthroplasty patients. The difference in KSS is, however, below the clinically important difference demonstrated by Lizaur‑Utrilla et al [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Significantly lower KOOS Symptoms, Pain, and QoL subscores after knee arthroplasty were demonstrated in the previous cartilage cohort. This concurs with the findings of Ansari et al [11] in a cohort of 21 previous microfracture patients with a mean 7.8 points lower improvement in the Knee Society Score (KSS) in the cartilage cohort than in a matched group of knee arthroplasty patients. The difference in KSS is, however, below the clinically important difference demonstrated by Lizaur‑Utrilla et al [25].…”
Section: Discussionsupporting
confidence: 91%
“…The difference in KSS is, however, below the clinically important difference demonstrated by Lizaur-Utrilla et al [25]. Ansari et al [11] did not report any power analysis prior to analysing the KSS results and the power analysis of the present study suggests that the Ansari study was underpowered.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Four studies [4043] investigated the long-term effect of various interventions and the progression to TKA. In one study, ninety-five patients with moderate to severe OA showed significant improvement in KOOS score post TKA [42].…”
Section: Resultsmentioning
confidence: 99%
“…However, compared to the control group, the TKA group had a fourfold increase in complications over the 12-month follow-up period. The other studies showed that previous knee surgery including microfracture leads to an increase in progression to a TKA [43] and post-traumatic KOA requiring TKA has a worse outcome than that for non-traumatic OA [41] (Table 1).…”
Section: Resultsmentioning
confidence: 99%